CHALLENGES AND OPPORTUNITIES IN LIBRARY AND INFORMATION SCIENCE EDUCATION IN WEST BENGAL - Sarkar, Ratan; Nand Kishore (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The information society's demands, the state of technology, and the changing information environment have all contributed to profound shifts in the way library and information science (LIS) programs in West Bengal are structured and taught. Many issues arise in library and information science (LIS) education as a result of the dynamic character of the field and the many cultural, social, and economic settings in which LIS programs operate. Focusing on LIS students and faculty in West Bengal, this research analyses the state of LIS education there and the possibilities and threats it faces. Using purposive sampling to guarantee a varied sample, 225 participants, including LIS students and professionals, were polled. t-test was applied. In order to strengthen library and information science education in the region, the results highlight the necessity of updating curricula, investing more in faculty development, and fostering better partnerships with business.